The Tumultuous Game of Legitimacy: Capital Contestation between Riggan, Mike, and Tabitha in Birdman (2014) - Alexei Wahyudiputra; Edi Dwi Riyanto (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2022)
The contemporary Hollywood cinematic landscape is commonly filled with popular films that seek mass legitimacy. It is different from theatrical works or Broadway that are specifically aimed at connoisseurs. The ample evidence of popular films infers that American cultural field constructs its logicality in effect of this system. It affects at how one distinctively perceives theatre or Broadway as “art” and films as “entertainment